Comparison of Lipase Production by Enterococcus faecium MTCC 5695 and Pediococcus acidilactici MTCC 11361 Using Fish Waste as Substrate: Optimization of Culture Conditions by Response Surface Methodology. (27th September 2012) - Ramakrishnan, Vrinda; Goveas, Louella Concepta; Narayan, Bhaskar; Halami, Prakash M.
Abstract : A medium using fish waste as substrate was designed for production of lipase by Enterococcus faecium MTCC 5695 and Pediococcus acidilactici MTCC 11361. Medium components and culture conditions (fish waste protein hydrolysate (FWPH) concentration, fish waste oil (FWO) concentration, pH, temperature, and fermentation time) which affect lipase production were screened using factorial (5 factors ∗ 2 levels) design of which FWPH concentration, FWO concentration, and fermentation time showed significance (P < 0.05 ). The levels of these factors were optimized further by Box-Behnken design using response surface methodology (RSM). Optimized conditions were found to be 5% v/v FWO, 0.15 mg/mL FWPH and 24 h of fermentation time for MTCC 5695, and 4% v/v FWO, 0.15 mg/mL FWPH and 24 h of fermentation for MTCC 11361, which were further validated. Under optimized conditions, MTCC 5695 and MTCC 11361 showed 3.15- (543.63 to 1715 U/mL) and 2.3- (214.74 to 493 U/mL) fold increase in lipase production, respectively, as compared to unoptimized conditions.